Performance comparison of mode-locked erbium-doped fiber laser with nonlinear polarization rotation and saturable absorber approaches - Ismail, M.A.; Tan, S.J.; Shahabuddin, N.S.; Harun, Sulaiman Wadi; Arof, Hamzah; Ahmad, Harith (IOP Publishing, 2012)
A mode-locked erbium-doped fiber laser (EDFL) is demonstrated using a highly concentrated erbium-doped fiber (EDF) as the gain medium in a ring configuration with and without a saturable absorber (SA). Without the SA, the proposed laser generates soliton pulses with a repetition rate of 12MHz, pulse width of 1.11 ps and energy pulse of 1.6 pJ. By incorporating SA in the ring cavity, the optical output of the laser changes from soliton to stretched pulses due to the slight change in the group velocity dispersion. With the SA, a cleaner pulse is obtained with a repetition rate of 11.3MHz, a pulse width of 0.58 ps and a pulse energy of 2.3 pJ.